A Phase II Randomized Trial (GO27827) of First‐Line FOLFOX Plus Bevacizumab with or Without the MET Inhibitor Onartuzumab in Patients with Metastatic Colorectal Cancer. (March 2017) - Bendell, Johanna C.; Hochster, Howard; Hart, Lowell L.; Firdaus, Irfan; Mace, Joseph R.; McFarlane, Joshua J.; Kozloff, Mark; Catenacci, Daniel; Hsu, Jessie J.; Hack, Stephen P.; Shames, David S.; Phan, See‐Chun; et al.
Abstract: Background: Dysregulated hepatocyte growth factor/mesenchymal‐epithelial transition (MET) signaling is associated with poor prognosis and resistance to vascular endothelial growth factor inhibition in metastatic colorectal cancer (mCRC). We report outcomes from a double‐blind, multicenter phase II trial of the MET inhibitor onartuzumab in combination with mFOLFOX‐6 and bevacizumab for mCRC (GO27827; NCT01418222). Materials and Methods: Patients were randomized 1:1 to receive onartuzumab (10 mg/kg intravenously [IV]) or placebo plus mFOLFOX‐6 and bevacizumab (5 mg/kg IV). Oxaliplatin was given for 8–12 cycles; other agents were continued until disease progression, unacceptable toxicity, or death. The primary endpoint was progression‐free survival (PFS) in the intent‐to‐treat (ITT) and MET immunohistochemistry (IHC) expression‐positive populations. Results: Between September 2011 and November 2012, 194 patients were enrolled. In September 2013, an interim analysis recommended stopping onartuzumab treatment due to lack of efficacy. At the time of the final analysis in February 2014, no significant improvement in PFS was seen with onartuzumab versus placebo in either the ITT or MET IHC‐positive populations. An improvement in PFS was noted in the MET IHC‐negative population. Neither overall survival nor response rate was improved with onartuzumab. The incidence of fatigue, peripheral edema, and deep vein thrombosis was increased with onartuzumab relative to placebo. Conclusion: Onartuzumab combined with mFOLFOX‐6 and bevacizumab did not significantly improve efficacy outcomes in either the ITT or MET IHC‐positive populations. MET expression by IHC was not a predictive biomarker in this setting. The Oncologist 2017;22:264–271 Implications for Practice: The addition of onartuzumab to mFOLFOX‐6 plus bevacizumab did not improve outcomes in patients with previously untreated metastatic colorectal cancer in this randomized, phase II study. Although initial results with onartuzumab were promising, a number of phase II/III clinical trials have reported a lack of improvement in efficacy with onartuzumab combined with standard‐of‐care therapies in several tumor types. Furthermore, negative study data have been published for rilotumumab and ficlatuzumab, both of which block hepatocyte growth factor binding to the mesenchymal‐epithelial transition (MET) receptor. MET immunohistochemistry was not a predictive biomarker. It remains to be seen if other biomarkers or small molecule inhibitors may be more appropriate for inhibiting this oncogenic pathway. Abstract : Treatment for advanced metastatic colorectal cancer has improved over the past decade with the addition of biologic agents to standard chemotherapy regimens, leading to increases in median overall survival. FOLFOX plus bevacizumab is now widely accepted as the standard first‐line treatment. To determine whether onartuzumab has a beneficial role in either unselected or MET‐selected populations with metastatic colorectal cancer, this phase II study was initiated to evaluate the combination of bevacizumab and mFOLOFOX6 with or without onartuzumab